Flammability of self-extinguishing kenaf/ABS nanoclays composite for aircraft secondary structure - Karunakaran, S.; Abang Abdul Majid, Dayang Laila; Mohd Tawil, M. Lufti (Institute of Physics Publishing, 2016)
This study investigates the flammability properties of kenaf fiber reinforced acrylonitrile butadiene styrene (ABS) with nanoclays composites. Natural fiber is one of the potential materials to be used with thermoplastic as a composite due to its attractive properties such as lightweight and strong. In this paper, flammability properties of this material are evaluated through Underwriters Laboratory 94 Horizontal Burning (UL94 HB), which has been conducted for both controlled and uncontrolled conditions, smoke density and limiting oxygen index tests (LOI). These flammability tests are in compliance with the Federal Aviation Regulation (FAR) requirement. The results from UL94 HB and smoke density tests show that the presence of nanoclays with effective composition of kenaf fiber reinforced ABS has enhanced the burning characteristics of the material by hindering propagation of flame spread over the surface of the material through char formation. Consequently, this decreases the burning rate and produces low amount of smoke during burning. On contrary, through LOI test, this material requires less oxygen to burn when exposed to fire, which hinders the enhancement of burning characteristics. This is due to burning mechanism exhibited by nanoclays that catalyzes barrier formation and flame propagation rate over the surface of the biocomposite material. Overall, these experimental results suggest that this biocomposite material is capable of self-extinguishing and possesses effective fire extinction. The observed novel synergism from the result obtained is promising to be implemented in secondary structures of aircraft with significant benefits such as cost-effective, lightweight and biodegradable self-extinguishing biocomposite.